Silencing VEGFR-2 Hampers Odontoblastic Differentiation of Dental Pulp Stem Cells - Janebodin, Kajohnkiart; Chavanachat, Rakchanok; Hays, Aislinn; Reyes Gil, Morayma (Frontiers in Cell and Developmental Biology, 2021)
Dental pulp stem cells (DPSCs) are a source of postnatal stem cells essential for maintenance and regeneration of dentin and pulp tissues. Previous in vivo transplantation studies have shown that DPSCs are able to give rise to odontoblast-like cells, form dentin/pulp-like structures, and induce blood vessel formation. Importantly, dentin formation is closely associated to blood vessels. We have previously demonstrated that DPSC-induced angiogenesis is VEGFR-2-dependent. VEGFR-2 may play an important role in odontoblast differentiation of DPSCs, tooth formation and regeneration. Nevertheless, the role of VEGFR-2 signaling in odontoblast differentiation of DPSCs is still not well understood. Thus, in this study we aimed to determine the role of VEGFR-2 in odontoblast differentiation of DPSCs by knocking down the expression of VEGFR-2 in DPSCs and studying their odontoblast differentiation capacity in vitro and in vivo. Isolation and characterization of murine DPSCs was performed as previously described. DPSCs were induced by VEGFR-2 shRNA viral vectors transfection (MOI = 10:1) to silence the expression of VEGFR-2. VEGFR-2 shRNA DPSCs expressed not only very low level of VEGFR-2, but also that of its ligand, VEGF-A, compared to control CopGFP DPSCs in both transcriptional and translational levels. In vitro differentiation of DPSCs in osteo-odontogenic media supplemented with BMP-2 (100 ng/ml) for 21 days demonstrated that CopGFP DPSCs, but not VEGFR-2 shRNA DPSCs, were positive for ALP staining and formed mineralized nodules positive for Alizarin Red S. The expression levels of dentin matrix proteins, dentin matrix protein-1, dentin sialoprotein, and bone sialoprotein, were also up-regulated in differentiated CopGFP DPSCs, compared to those in VEGFR-2 shRNA DPSCs, suggesting an impairment of odontoblast differentiation in VEGFR-2 shRNA DPSCs. In vivo subcutaneous transplantation of DPSCs with hydroxyapatite demonstrated that CopGFP DPSCs were able to differentiate into elongated and polarized odontoblast-like cells forming loose connective tissue resembling pulp-like structures with abundant blood vessels. On the other hand, in VEGFR-2 shRNA DPSC transplants, odontoblast-like cells were not observed. Collagen fibers were seen in replacement of dentin/pulp-like structures. These results indicate that VEGFR-2 may play an important role in dentin regeneration and highlight the potential of VEGFR-2 modulation to enhance dentin regeneration.